Significance of Immune Response Patterns in Lymph Nodes Draining Breast Carcinoma - Mr. Thrilok H, Dr. Prema Saldanha, Dr. Taqiya Nuzhath, (International Journal of Innovative Research in Medical Science, 2017)
Background: Axillary lymph node enlargement in breast cancer may be caused by metastasis or may be due to reactive hyperplasia. It is assumed that the histological analysis of the patterns in the regional lymph nodes draining the tumor could elucidate the immunological host-tumor relationship and provide additional information on patient survival. Material and Methods: Retrospective study on lymph nodes received with mastectomy specimens. The lymph nodes both involved and uninvolved by metastasis were selected. The morphological responses in the uninvolved lymph nodes were classified into groups comprising of either a single predominant pattern i.e., lymphocyte predominance, germinal centre predominance, or sinus histiocytosis according to the WHO proposal. The tumor size, grade, stage and the ER/PR and HER2-neu status were recorded and correlated with the patterns. Results: Forty six cases were studied with a total of 551 lymph nodes. Out of these, 123 lymph nodes had metastatic carcinoma & 428 lymph nodes had no metastasis. The patients were in the age range 22-78years. Most of the cases had a tumor size of 2-5 cms. Maximum cases had a microscopic grade of II and pathological TNM stage II. Sinus histiocytosis was the common pattern in all the patients followed by Germinal Centre Predominance and Lymphocyte Predominance. The predominance of the sinus histiocytosis pattern was found to be statistically significant, but there was no association with the pattern and tumor size, grade, stage, ER/PR and Her2-neu status. Conclusion: Reactive patterns in the regional lymph nodes could be helpful in providing information on patient prognosis